Dominantly inherited cleft lip and palate in two families. Issue 6 (June 1989) - Temple, K; Calvert, M; Plint, D; Thompson, E; Pembrey, M
Abstract : Two families with non-syndromic cleft lip and cleft palate are described. The linear pattern of inheritance through several generations is difficult to explain by conventional multifactorial models. The pedigrees strengthen the suggestion that a dominantly inherited mutation exists with a major influence on clefting of the lip and palate alone.